Fluoride, calcium and magnesium intake in children living in a high-fluoride area in Ethiopia. Intake through food - M. K. MALDE, L. ZERIHUN, K. JULSHAMN, & K. BJORVATN (Paediatric Dentistry, 2004)
In general, drinking water, beverages, toothpaste and other caries preventive agents are regarded as the main dietary contributors to human fluoride intake.